Morally Relevant Similarities and Differences Between Children and Dementia Patients as Research Subjects: Representation in Legal Documents and Ethical Guidelines. - Jongsma, Karin; Bos, Wendy; Vathorst, Suzanne (Bioethics, 2015)
Children and adults with dementia are vulnerable populations. Both groups are also relatively seldom included in biomedical research. However, including them in clinical trials is necessary, since both groups are in need of scientific innovation and new therapies. Their dependence and limited decision-making capacities increase their vulnerability, necessitating extra precautions when including them in clinical trials. Beside these similarities there are also many differences between the groups. The most obvious one is that children have an entire life ahead of them and will become persons with certain ideals and preferences, while adults with dementia have lived a life in which they have expressed their ideals and preferences. Some of the available research guidelines recognize these differences, setting one list of specific requirements for groups of incapacitated adults and another list for children. Other documents, however, do not differentiate and only set requirements for subjects unable to consent as a single category of subjects. In this article we analyse to what extent the similarities and differences between the two groups are represented in legal documents and ethical guidelines. The article presents an overview and an analysis of the requirements for doing research with children and dementia patients. We conclude with suggestions about how to better incorporate the morally relevant aspects of these two groups in legislation and ethical guidelines.